Examining the Securitization of Refugees in Denmark: The Impact of Right-Wing Political Agendas - Estriani, Heavy Nala; Qomaria, Nurul (Hasanuddin University, 2024)
The influx of migrants into Europe in 2015 has led to a sharp rise in support for right-wing groups. Denmark is a prime example of this tendency, as the Danish People's Party (Dansk Folkeparti, DF) scored its highest-ever election success and emerged as the second-largest party in the 2015 Denmark’s general election, greatly impacting immigration and refugee decisions. The dominance of right-wing parties has, in turn, influenced Denmark’s policy direction towards asylum seekers and refugees. Anti-refugee and anti-asylum seeker narratives propagated by these parties reflect elements of securitization employed by the Danish government in addressing refugee issues. This study aims to examine the changes in Denmark’s government policies toward refugees. It seeks to analyze the elements within the concept of securitization that underpin the shifts in anti-immigration narratives particularly post-2015. This assumption is based on two factors; the anti-immigration policies advocated by right-wing parties and the perception of refugees as threats to security.